A Multi-Centre, Single-Arm Clinical Study to Confirm Safety and Performance of PuraStat®, for the Management of Bleeding in Elective Carotid Artery Surgery - Katherine M. Stenson MA, MBBS, MD, FRCS; Ian M. Loftus MD, FRCS; Ian Chetter MD, FRCS; Inge Fourneau PhD, MD; Stephen Cavanagh FRCS; Colin Bicknell MD, FRCS; Paros Loftus MBBS (Clinical and Applied Thrombosis/Hemostasis, 2022)
Anastomotic bleeding in vascular surgery can be difficult to control. Patients, in particular those undergoing carotid surgery, have often been started on treatment with dual antiplatelet agents and receive systemic heparinization intraoperatively. The use of local hemostatic agents as an adjunct to conventional methods is widely reported. 3-D Matrix’s absorbable hemostatic material RADA16 (PuraStat®), is a fully synthetic resorbable hemostatic agent. The aim of this study is to confirm the safety and performance of this agent when used to control intraoperative anastomotic bleeding during carotid endarterectomy (CEA). A prospective, single-arm, multicenter study involving 65 patients, undergoing CEA, in whom the hemostatic agent was applied to the suture line after removal of arterial clamps. Patients were followed up at 24 h, discharge, and one month after surgery. Time to hemostasis was measured as the primary endpoint. Secondary endpoints included hemostasis efficacy and safety outcomes, blood loss, intraoperative and postoperative administration of blood products, and incidence of reoperation for bleeding. A total of 65 cases (51 male and 14 female) undergoing CEA, utilizing patch reconstruction (90. 8%), eversion technique (6.1%), and direct closure (3.1%) were analyzed. All patients received dual antiplatelet therapy preoperatively and were administered systemic intravenous heparin intraoperatively, as per local protocol. The mean time to hemostasis was 83 s ± 105 s (95% CI: 55-110 s). Primary hemostatic efficacy was 90.8%. The mean volume of product used was 1.7 mL ± 1.1 mL. Hemostasis was achieved with a single application of the product in 49 patients (75.3%). Two patients required a transfusion of blood products intraoperatively. There were no blood product transfusions during the postoperative period. The intraoperative mean blood loss was 127 mL ± 111.4 mL and postoperatively, the total mean drainage volume was 49.0 mL ± 51.2 mL. The mean duration of surgery was 119 ± 35 min, and the mean clamp time was 35 min 12 s ± 19 min 59 s. In 90.8% of patients, there was no presence of hematoma at 24 h postoperatively. Three returned to theatre due to bleeding (2 in the first 24 h), however, none of these cases were considered product related. Overall, there were no device-related serious adverse events (SAE) or unanticipated device-related SAEs reported. Use of the hemostatic agent PuraStat® is associated with a high rate of hemostatic efficacy (90.8%) and a short time to hemostasis. The safety of the product for use on vascular anastomoses has been demonstrated.